EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE CREATIVE PROBLEM SOLVING (CPS) MELALUI MACROMEDIA FLASH 8 DITINJAU DARI KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA DI SMA NEGERI 1 ANGKOLA SELATAN - Siti Hamimah Harahap (JURNAL MathEdu (Mathematic Education Journal), 2019)
This study aims to know whether there is a significant influence of using cooperative learning model of CPS type through macromedia flash 8 on students’ mathematical problem solving ability at tenth grade students of SMA Negeri 1 Angkola Selatan. The research was conducted by using experimental method with 36 students as the sample and they were taken by using cluster random sampling technique from 103 students. Test and observation were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using CPS type through macromedia flash 8 was 3.30 (very good category) and b) the average of students’ mathematical problem solving ability before using CPS type through macromedia flash 8 was 49.86 (fair category) and after using CPS type through macromedia flash 8 was 73.68 (good category). Furthermore, based on inferential statistic by using pair sample ttest, and helping SPSS Version 23, the result showed the significant value was less than 0.05 (0.000<0.05). It means, there is the significant influence of of using cooperative learning model of CPS type through macromedia flash 8 on students’ mathematical problem solving ability at tenth grade students of SMA Negeri 1 Angkola Selatan.